Optimization of Radial Distribution Network with Distributed Generation Using Particle Swarm Optimization Considering Load Growth - Abdullah, M.A.A. (Springer Science and Business Media Deutschland GmbH, 2022)
This article presents a combination of particle swarm optimization (PSO) algorithm and the backward/forward sweep power flow (BFSPF) approach to determine the optimal bus location and sizeÂ of distributed generation (DG) in a radial distribution network (RDN) considering the load growth. The analysis of the proposed optimization framework is performed using MATLAB and tested on the 33âbus RDN subject to minimize the power losses. The solutions accomplished through theÂ experiments considering four case studies show significant reductionsÂ in the systemâsÂ total power loss and improvement in desired bus voltage profiles. With the installation of DG, the percentage of reduction in power loss is 47.38 compared to the systemâs power loss without DG. The DG size and location to be installed are determined at the 6th bus location with 2.59Â MW. The results show that power losses will increase with the increase in load demand. The findings reveal that load growth does not influence the optimal location of the DG. However, the sizes of DGs need to be revised when considering growth in load conditions. Â© 2022, The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd.